International Society of Sports Nutrition Position Stand: beta-hydroxy-beta-methylbutyrate (HMB) - Wilson, Jacob M (BioMed Central, 2013)
Position Statement: The International Society of Sports Nutrition (ISSN) bases the following position stand on a critical analysis of the literature on the use of beta-hydroxy-beta-methylbutyrate (HMB) as a nutritional supplement. The ISSN has concluded the following. 1. HMB can be used to enhance recovery by attenuating exercise induced skeletal muscle damage in trained and untrained populations. 2. If consuming HMB, an athlete will benefit from consuming the supplement in close proximity to their workout. 3. HMB appears to be most effective when consumed for 2 weeks prior to an exercise bout. 4. Thirty-eight mg·kg·BM(-1) daily of HMB has been demonstrated to enhance skeletal muscle hypertrophy, strength, and power in untrained and trained populations when the appropriate exercise prescription is utilized. 5. Currently, two forms of HMB have been used: Calcium HMB (HMB-Ca) and a free acid form of HMB (HMB-FA). HMB-FA may increase plasma absorption and retention of HMB to a greater extent than HMB-CA. However, research with HMB-FA is in its infancy, and there is not enough research to support whether one form is superior. 6. HMB has been demonstrated to increase LBM and functionality in elderly, sedentary populations. 7. HMB ingestion in conjunction with a structured exercise program may result in greater declines in fat mass (FM). 8. HMB’s mechanisms of action include an inhibition and increase of proteolysis and protein synthesis, respectively. 9. Chronic consumption of HMB is safe in both young and old populations.